THE INFLUENCE OF COORDINATION AND STANDARD OPERATING PROCEDURES ON EMPLOYEE PERFORMANCE THROUGH MOTIVATION AS INTERVENING VARIABLE (STUDY ON PROTOCOL AND COMMUNICATION DEPARTMENT OF BANYUWANGI REGENCY) - Fadlillah, Dzikri; Ni Nyoman Putu Martini G; Trias Setyowati (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This research is motivated by issues related to the implementation of E-Guest Book in Banyuwangi Regency, where there is a significant gap between visit data recorded in the system and manual data. The study aims to analyze the influence of coordination and SOP on employee performance through work motivation as an intervening variable in the Protocol and Leadership Communication Section of Banyuwangi Regency. Method: The research method uses quantitative descriptive and verification approaches by analyzing relationships between variables. Results: The results show that coordination and SOP have positive and significant effects on work motivation and employee performance, both directly and indirectly. Work motivation is proven to act as an intervening variable that strengthens the relationship between coordination and SOP on employee performance. Novelty: It is recommended that organizations conduct periodic evaluations of SOPs, develop more effective communication systems, provide SOP understanding training, and create better reward systems to improve employee motivation and performance.